2006
DOI: 10.1002/pssb.200669110
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, isolation and characterization of new endohedral fullerenes M@C72 (M = Eu, Sr, Yb)

Abstract: We report on new europium, strontium and ytterbium endohedral fullerene cages of the type Eu@C 72 , Sr@C 72 and Yb@C 72 . Single isomers of Eu@C 72 -I, Sr@C 72 -I, Sr@C 72 -II and Yb@C 72 -I were isolated by multi-step HPLC for the first time. Details of their synthesis, separation and characterization by LDI-TOF mass spectrometry and UV-vis will be discussed. Additionally, EPR spectroscopy of Eu@C 72 -I was performed. A second isomer of europium and ytterbium endohedral C 72 , Eu@C 72 -II and Yb@C 72 -II, has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 9 publications
1
14
0
3
Order By: Relevance
“…The onset of the absorption is 1044 nm, and several characteristic peaks at 448, 490, 540, 613 and 789 nm are observed. The characteristic absorptions of YCN@C 2v (11188)‐C 72 are very close to those of M@C 72 −1 (M=Eu, Sr, Yb), implying that these metallofullerenes have the same cage structure. The strong absorption peak at 1044 nm is assigned to the HOMO→LUMO transition, corresponding to an optical band gap of 1.19 eV.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The onset of the absorption is 1044 nm, and several characteristic peaks at 448, 490, 540, 613 and 789 nm are observed. The characteristic absorptions of YCN@C 2v (11188)‐C 72 are very close to those of M@C 72 −1 (M=Eu, Sr, Yb), implying that these metallofullerenes have the same cage structure. The strong absorption peak at 1044 nm is assigned to the HOMO→LUMO transition, corresponding to an optical band gap of 1.19 eV.…”
Section: Resultsmentioning
confidence: 99%
“…[17][18][19] Considerable experimental and theoretical investigations have been devoted on the C 72 -based EMFs. Endohedral fullerenes M 2 @C 72 (M5 La, Ce, Pr), [20][21][22] Sc 2 S@C 72 , [23] Sc 2 C 2 @C 72 , [24] La@C 72 , [25] and M@C 72 (M5Ca, Eu, Sr, Yb) [26][27][28] have been isolated. In EMFs, electron transfer from the encased metallic species to the fullerene cage takes place.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, density-functional theory (DFT) computations are carried out on another observed [ 17 , 18 ] C -based metallofullerene, namely isomers of Eu@C , in order to clarify their structures and stabilities and to enrich the knowledge on the whole C -based endohedral family [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ], considering IPR, classical non-IPR, and heptagon-containing structures [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Later on, C 72 monometallofullerenes based on other divalent metals such as Yb and Eu, which result in af ormal two-electron transfer to the carbon cage,w ere also isolated and characterized by Vis/NIR spectroscopy.Y b@C 72 and Eu@C 72 exhibited similar absorption features in the NIR region as one of the Ca@C 72 isomers. [61] In 2013, Yang and Zhao proposed by means of density-functional theory (DFT) calculations that Yb@C 72 adopted two non-IPR cage isomers, C 2v (11188)-C 72 and C 2 (10612)-C 72 ,c ontaining ap air of DFPs. [62] Similarly,in2017 Slanina et al computed six isomers of Eu@C 72 and concluded that the two DFP-containing non-IPR cage isomers,namely, C 2v (11188)-C 72 and C 2 (10612)-C 72 , were favored for Eu@C 72 .…”
Section: Stabilization Of Double Fused Pentagons (Dfps)mentioning
confidence: 99%